2012
DOI: 10.1115/1.4004740
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control of Noise and Instability in a Swirl-Stabilized Combustor With the Use of High-Strength Porous Insert

Abstract: Swirl-stabilized combustion and porous inert medium (PIM) combustion are two methods that have been used extensively, although independently, for flame stabilization. In this study, the two concepts are combined so that the porous insert serves as a passive device to mitigate combustion noise and instabilities. A properly shaped PIM is placed within the combustor to directly influence the turbulent flow field and vortical and/or shear layer structures associated with the outer recirculation zone and inner reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The pore size was selected such that any reactions within the porous media will be quenched. The sizing was selected from findings in Sequera and Agrawal 35 where the amount of burning within the porous structure could be eliminated with proper selection of pore size. From Ref., 35 thermal radiation of the porous media in the visible spectrum was observed when pore sizes were sufficiently large enough for reactions to occur within the porous structure, which would heat the porous structure to a temperature hot enough to thermally radiate in the visible spectrum.…”
Section: Phase Averaged Abel Inverted Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pore size was selected such that any reactions within the porous media will be quenched. The sizing was selected from findings in Sequera and Agrawal 35 where the amount of burning within the porous structure could be eliminated with proper selection of pore size. From Ref., 35 thermal radiation of the porous media in the visible spectrum was observed when pore sizes were sufficiently large enough for reactions to occur within the porous structure, which would heat the porous structure to a temperature hot enough to thermally radiate in the visible spectrum.…”
Section: Phase Averaged Abel Inverted Resultsmentioning
confidence: 99%
“…The sizing was selected from findings in Sequera and Agrawal 35 where the amount of burning within the porous structure could be eliminated with proper selection of pore size. From Ref., 35 thermal radiation of the porous media in the visible spectrum was observed when pore sizes were sufficiently large enough for reactions to occur within the porous structure, which would heat the porous structure to a temperature hot enough to thermally radiate in the visible spectrum. Although some reactions may be taking place inside the core region, the high velocity in this region will be larger than the flame speed, so this effect is minimal, if any.…”
Section: Phase Averaged Abel Inverted Resultsmentioning
confidence: 99%
“…Combustion noise results from the propagation of broadband sound waves generated by heat release rate fluctuations in a turbu lent flow field [1], Putnam [2] and Strahle [3] developed analytical models and empirical data to correlate sound pressure level (SPL) with combustion parameters such as air-fuel ratio, fuel type, reac tants flow rate, and geometry in nonpremixed combustion sys tems. Combustion noise results from the propagation of broadband sound waves generated by heat release rate fluctuations in a turbu lent flow field [1], Putnam [2] and Strahle [3] developed analytical models and empirical data to correlate sound pressure level (SPL) with combustion parameters such as air-fuel ratio, fuel type, reac tants flow rate, and geometry in nonpremixed combustion sys tems.…”
Section: T Im E -R E S O LV E D P a Rtic Le Im A G E V E Lo C Im E Trmentioning
confidence: 99%
“…Computations revealed that the porous insert eliminates the corner recirculation zone, strengthens the swirling flow and central recirculation zone, and directs some combustion products through the porous insert. Sequera and Agrawal [1] and Williams and Agrawal [30] demonstrated the effectiveness of porous insert to reduce combustion noise and/or instabilities for a wide range of operating conditions. In these experiments, at fixed airflow rate of 6.24 g/s (300 SLPM), a divergent PIM ring with pore den sity of 18 ppcm (45 ppi) provided the greatest reduction in the total SPLs.…”
Section: (A ) S C H E M a T Ic D Ia G R A M A N D (B) P H O T O G R Amentioning
confidence: 99%
“…PIM was shown to eliminate a prevalent instability, near 500 Hz, that occurred under several conditions. Agrawal and coworkers [2,3,9,10] have shown that the use of several configurations of PIM in a high-pressure combustion chamber is advantageous for noise mitigation under various combustion conditions. Computational results were used to describe the effect of PIM on the combustor flowfield.…”
Section: Introductionmentioning
confidence: 99%